Interaction of step length and step rate during sprint running - Hunter, J. P.; Marshall, R. N.; McNair, P. J. (Medicine & Science in Sports & Exercise, 2004)
A "negative interaction" between step length and step rate refers to an increase in one factor resulting in a decrease in the other. PURPOSES: There were three main purposes: a) to investigate the relative influence of the determinants of step length and step rate, b) to determine the sources of negative interaction between step length and step rate, and c) to investigate the effects of manipulation of this interaction. METHODS: Thirty-six athletes performed maximal-effort sprints. Video and ground reaction force data were collected at the 16-m mark. Sprint velocity, step length, step rate, and their underlying determinants were calculated. Analyses included correlations, multiple linear regressions, paired t-tests, and a simple simulation based on alterations in flight determining parameters. RESULTS: A wide range of step length and step rate combinations was evident, even for subgroups of athletes with similar sprint velocities. This was partly due to a negative interaction that existed between step length and step rate; that is, those athletes who used a longer step length tended to have a lower step rate and vice versa. Vertical velocity of takeoff was the most prominent source of the negative interaction. CONCLUSIONS: Leg length, height of takeoff, and vertical velocity of takeoff are all possible sources of a negative interaction between step length and step rate. The very high step lengths and step rates achieved by elite sprinters may be possible only by a technique that involves a high horizontal and low vertical velocity of takeoff. However, a greater vertical velocity of takeoff might be of advantage when an athlete is fatigued and struggling to maintain a high step rate.